LIPOSUCTION KEMAJUAN DALAM TEHNIK OPERASI - Ngantung, Jan (UNIVERSITAS SAM RATULANGI, 2009)
Abstract: Liposuction -lipoplasty (fat modelling), liposculpture, suction lipectomy, lipo (suction-assisted fat removal)- is a cosmetic surgery operation that removes fat from many different sites in the human body. After thirty years of improvements, more fat cells can now be removed more easily, with less blood loss, less discomfort, and less risks. Recent developments suggest that the recovery period can be shortened as well. As with any surgery, there are certain risks, beyond temporary and minor side effects. Careful patient selection and the usage of clinically proven procedure minimize their occurrences. Liposuction procedures depend on available choices of operations and the condition of patients. Key words: Liposuction, fat, operation technique. Abstrak: Liposuction merupakan tehnik operasi kosmetik yang mengeluarkan lemak dari berbagai tempat di dalam tubuh. Setelah perkembangan selama 30 tahun maka lebih banyak sel-sel lemak di dalam tubuh yang dapat dikeluarkan dengan lebih mudah, lebih sedikit terjadi kehilangan darah, serta lebih kurang ketidak nyamanan dan resiko. Demikian pula masa penyembuhan menjadi lebih singkat. Seperti halnya tindakan operasi lainnya, liposuction juga tidak lepas dari terjadinya resiko. Dengan seleksi pasien yang ketat dan penggunaan tehnik operasi yang telah terbukti hal tersebut dapat ditekan. Pemilihan jenis liposuction disesuaikan dengan jenis tindakan operasi yang tersedia dan keadaan pasien. Kata kunci: Liposuction, lemak, tehnik operasi.